CS-36 Recommendations for the assessment of systemic lupus erythematosus in canada. (August 2018) - Keeling, Stephanie; Alabdurubalnabi, Zainab; Avina-Zubieta, Antonio; Barr, Susan; Bergeron, Louise; Bernatsky, Sasha; Bourre-Tessier, Josiane; Clarke, Ann; Baril-Dionne, Alexandra; Dutz, Jan; Ensworth, Stephanie; Fifi-Mah, Aurore; et al.
Abstract : Background: To develop GRADE-based recommendations for the diagnosis and monitoring of systemic lupus erythematosus patients in Canada. Methods: Recommendations were developed using the GRADE (Grading of Recommendations, Assessment, Development and Evaluation) approach. The Canadian SLE Working Group (panel of Canadian rheumatologists and patient representative from CAPA (Canadian Arthritis Patient Alliance)) was created. A series of questions for recommendation development were identified based on the results of a survey of SLE practice patterns of members of the Canadian Rheumatology Association (CRA). Systematic literature reviews of randomized controlled trials and observational studies were conducted. Evidence to Recommendation Tables were prepared and presented to the panel at two face-to-face meetings for discussion and voting during and post-meeting online. Results: There were a total of fourteen recommendations for assessing and monitoring lupus patients (table 1). Three recommendations focused on disease activity and damage assessment suggesting that a validated disease activity score per visit and annual damage score were important in evaluating the patient. One strong recommendation was made for cardiovascular risk assessment with conditional recommendations for osteoporosis (2) and osteonecrosis (1). Three conditional recommendations were made regarding peripartum assessments, one on cervical cancer screening and two on hepatitis B and C screening. A strong recommendation was made for annual influenza vaccination. Conclusions: These are the first GRADE-based recommendations for the diagnosis and monitoring of SLE internationally. Evidence is largely of moderate to low quality resulting in more conditional versus strong recommendations. Further studies of higher quality and special attention to pediatric lupus populations are needed. Acknowledgements: The authors are members of the Canadian SLE Working Group which was created to develop these recommendations.